2007
DOI: 10.1186/gb-2007-8-9-r179
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis reveals the major driving forces of bacterial life in the rhizosphere

Abstract: Bacterial life in the rhizosphere

A global analysis of Pseudomonas putida gene expression performed during the interaction with maize roots revealed how a bacterial population adjusts its genetic program to the specific conditions of this lifestyle.

Abstract Background: Mutualistic interactions less well known than those between rhizobia and legumes are commonly found between plants and bacteria, frequently pseudomonads, which colonize roots and adjacent soil areas (the rhizosphere).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
163
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(175 citation statements)
references
References 47 publications
12
163
0
Order By: Relevance
“…This might be due to reductive evolution and could reflect a more stringent association with its plant host, although smaller size is not specific to A1501 and was reported for other P. stutzeri strains that do not necessarily have the same lifestyle (38). In addition, P. putida KT2440, which is also a rhizospheric strain, has a much larger genome (3,39) (Table 1). We identified a set of 487 genes common to other Pseudomonas and absent in the A1501 genome, suggesting loss of functions in A1501, as noted for the alginate biosynthesis gene cluster and for fluorescent siderophore production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be due to reductive evolution and could reflect a more stringent association with its plant host, although smaller size is not specific to A1501 and was reported for other P. stutzeri strains that do not necessarily have the same lifestyle (38). In addition, P. putida KT2440, which is also a rhizospheric strain, has a much larger genome (3,39) (Table 1). We identified a set of 487 genes common to other Pseudomonas and absent in the A1501 genome, suggesting loss of functions in A1501, as noted for the alginate biosynthesis gene cluster and for fluorescent siderophore production.…”
Section: Discussionmentioning
confidence: 99%
“…12 and 14, their actual involvement in colonization remains to be established. Recent work in the rhizospheric P. pudtia KT2440 identified 91 genes up-regulated in the presence of maize exudates (39), and 31 of them are conserved in A1501 (including regulators, transport systems, stress response, and chemotaxis) (data not shown). Present knowledge of the genome should help in elucidating regulatory mechanisms that control the association with the host plant, thus enabling better comprehension of mechanisms of nitrogen transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the stress response genes in PGPR organisms by the root exudates was reported in a previous study (Matilla et al, 2007). Through the observed up-regulation of the SasA alarmone biosynthesis pathway it was hypothesized that the level of (p)ppGpp might be increased in bacteria treated with the root exudates.…”
Section: Gene Expression Profilingmentioning
confidence: 94%
“…The phenols might end up in the rhizosphere from decaying roots or as root exudates and sustain the detected diverse ring-cleavage community including endophytic bacteria in the root. Very recently, it has been shown that Pseudomonas type aromatic degrading genes are upregulated in corn rhizosphere indicating that corn root exudates contain aromatic compounds (Matilla et al, 2007). Simultaneous assay of 16S rRNA and ring-cleavage marker genes illustrated contrasting rhizosphere effects at different bacterial community levels.…”
Section: Discussionmentioning
confidence: 99%